TELECOMMUNICATION AND ECONOMIC GROWTH - Assylbek, Yerbolat (Nazarbayev University School of Sciences and Humanities, 2017)
The study examines the evidence of the impact of the telecommunication infrastructure on economic growth. First, the paper investigates relationship between the mobile/land-line phones and the economic growth by using Arellano-Bond difference generalized method of moments (GMM) estimator. Like a few previous studies, this paper takes into account potential endogeneity between economic growth and telecommunications variables. At the same time, this study pays attention of varying degree of land-line penetration and mobile phones expansion. The marginal impact from using mobile phones is higher where the traditional fixed-phones phones are used less. The results show that mobile phones play an important role in economic development across 29 countries from 2002 to 2015. The results are consistent with previous studies.
Keywords: telecommunications; economic growth